Association between Y402H, E318D and R102G polymorphisms of complement proteins genes and the response to intravitreal anti-VEGF treatment in patients with neovascular age-related macular degeneration - Kubicka-Trząska, Agnieszka; Karska-Basta, Izabella; Kobylarz, Joanna; Dziedzina, Sylwia; Sanak, Marek; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Aim : To analyze the correlation between the E318D rs9332739 polymorphism of the C2 complement factor; R102G rs2230199 polymorphism of the C3 complement factor as well as the Y402H rs1061170 polymorphism of the CFH complement factor and risk of AMD as well as the response to anti-VEGF therapy. Material and methods : 106 patients with age-related macular degeneration treated with intravitreal ranibizumab or bevacizumab were enrolled. The response to treatment was assessed at 4 weeks intervals for 6 months and was based on the results of best corrected visual acuity and central retinal thickness measurements compared to the respective baseline values. The control group consisted of 58 healthy volunteers. The testing was performed using genetic probes (TaqMan Applied Biosystems) in all cases. Results : E318D (C2) and R102G (C3) polymorphisms were not associated with age-related macular degeneration. The genotype CC of Y402H (CFH) polymorphism was more frequent in patients with age-related macular degeneration as compared to controls [OR=3.09 (1.28–7.49); p=0.0069]. At the last follow-up, patients with age-related macular degeneration positive for the CC rs1061170 CFH genotype presented with worse best corrected visual acuity and increased central retinal thickness as compared to their counterparts negative for this genotype [OR=7.67 (1.77–33.12), p=0.0052]. Among 25.47% of “non-responders”, the CC rs1061170 CFH genotype was present in 51.8% of cases. In patients with the TT rs1061170 CFH genotype the final best corrected visual acuity was better and a significant reduction of central retinal thickness was demonstrated in all those cases, as compared to subjects with the CC rs1061170 CFH genotype [OR=0.31 (0.11-0.84), p=0.0194]. Conclusions : The study showed that the CC rs1061170 CFH genotype may be associated with the age-related macular degeneration. Additionally, the CC rs1061170 CFH genotype may promote a negative response to anti-VEGF treatment, while patients with the TT rs1061170 CFH genotype showed better functional and structural response to anti-VEGF agents.